Classes, social struggles and public policies: Inflections to the brazilian working class - Silva , Adriana Brito da; Honorato , Andreia Agda Silva; Lima Sobrinho, Jodeylson Islony de; Santos, Thiago Aparecido Aranha dos (Seven Editora, 2023)
This article proposes a debate about social classes, social struggles and public policies based on the societal context that demarcates Brazil in the post-coup period of 2016, especially from 2018 to 2022 when social inequality worsens, the dismantling of public policies, mainly the demobilization of the political organization of the working class, having in return for rights,  deep marks of neo-fascism and the naturalization of barbarism, impacting the social reality and the population's way of life. The objective is to provoke debate and reflection on the political tricks and maneuvers that intensify inequality and social injustice in the country, concomitantly, on the demobilization strategies of the working class, however, to point out some triggers for new paths for the period that enters 2023 of the so-called reconstruction. This is a bibliographic, exploratory and qualitative study, whose analyzes are based on the critical social theoretical perspective and resulting in some clues relating to social participation as a possibility of social control and resistance in the face of a dismantling engendered in the country's history. DOI:https://doi.org/10.56238/sevened2023.006-080